Novel Majeed Syndrome–Causing LPIN2 Mutations Link Bone Inflammation to Inflammatory M2 Macrophages and Accelerated Osteoclastogenesis. Issue 6 (9th May 2021) - Bhuyan, Farzana; de Jesus, Adriana A.; Mitchell, Jacob; Leikina, Evgenia; VanTries, Rachel; Herzog, Ronit; Onel, Karen B.; Oler, Andrew; Montealegre Sanchez, Gina A.; Johnson, Kim A.; Bichell, Lena; Marrero, Bernadette; et al.
Abstract : Objective: To identify novel heterozygous LPIN2 mutations in a patient with Majeed syndrome and characterize the pathomechanisms that lead to the development of sterile osteomyelitis. Methods: Targeted genetic analysis and functional studies assessing monocyte responses, macrophage differentiation, and osteoclastogenesis were conducted to compare the pathogenesis of Majeed syndrome to interleukin‐1 (IL‐1)–mediated diseases including neonatal‐onset multisystem inflammatory disease (NOMID) and deficiency of the IL‐1 receptor antagonist (DIRA). Results: A 4‐year‐old girl of mixed ethnic background presented with sterile osteomyelitis and elevated acute‐phase reactants. She had a 17.8‐kb deletion on the maternal LPIN2 allele and a splice site mutation, p.R517H, that variably spliced out exons 10 and 11 on the paternal LPIN2 allele. The patient achieved long‐lasting remission receiving IL‐1 blockade with canakinumab. Compared to controls, monocytes and monocyte‐derived M1‐like macrophages from the patient with Majeed syndrome and those with NOMID or DIRA had elevated caspase 1 activity and IL‐1β secretion. In contrast, lipopolysaccharide‐stimulated, monocyte‐derived, M2‐like macrophages from the patient with Majeed syndrome released higher levels of osteoclastogenic mediators (IL‐8, IL‐6, tumor necrosis factor, CCL2, macrophage inflammatory protein 1α/β, CXCL8, and CXCL1) compared to NOMID patients and healthy controls. Accelerated osteoclastogenesis in the patient with Majeed syndrome was associated with higher NFATc1 levels, enhanced JNK/MAPK, and reduced Src kinase activation, and partially responded to JNK inhibition and IL‐1 (but not IL‐6) blockade. Conclusion: We report 2 novel compound heterozygous disease‐causing mutations in LPIN2 in an American patient with Majeed syndrome. LPIN2 deficiency drives differentiation of proinflammatory M2‐like macrophages and enhances intrinsic osteoclastogenesis. This provides a model for the pathogenesis of sterile osteomyelitis which differentiates Majeed syndrome from other IL‐1–mediated autoinflammatory diseases.